1993
DOI: 10.1111/j.1471-4159.1993.tb07451.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Conditions Differentially Regulate the Expression of α‐Amino‐3‐Hydroxy‐5‐Methylisoxazole‐4‐Propionate (AMPA) Receptor Subunits in Cultured Neurons

Abstract: We have studied the expression of alpha-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptor subunits in cultured cerebellar granule cells [7 days in vitro (DIV)] grown in medium containing different concentrations of K+ (10, 25, or 40 mM) with or without 100 microM N-methyl-D-aspartate (NMDA; added once after 2 DIV). All these conditions are known to influence maturation and survival of granule cells, as well as the functional expression of NMDA receptors during development in culture. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 34 publications
5
42
1
Order By: Relevance
“…Almost without exception, however, cultures are grown in media containing elevated KCl (or NMDA) because it enhances long-term survival compared with those grown in physiological media (Gallo et al, 1987). This is despite mounting evidence that continually depolarized cultures undergo numerous adaptations, including perturbed patterns of AMPA (Condorelli et al, 1993), NMDA (Vallano et al, 1996), and GABA (Mellor et al, 1998) receptor subunit expression; abnormal induction of inositol 1,4,5-trisphosphate receptor (Choi et al, 2004); calpain-mediated down-regulation of Ca 2ϩ /calmodulin-dependent protein kinase type IV (Tremper-Wells and Vallano, 2005), a net decrease in synaptic vesicles (Urakubo et al, 2003); suppression of spontaneous synaptic activity and action potentials (Mellor et al, 1998); reduced VDCC currents; and increased susceptibility to death upon activity reduction (Moulder et al, 2003). On the other hand, a significant proportion of granule neurons grown in medium containing 5 mM KCl require both tetrodotoxin-sensitive Na ϩ currents and active NMDA receptors for their survival (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Almost without exception, however, cultures are grown in media containing elevated KCl (or NMDA) because it enhances long-term survival compared with those grown in physiological media (Gallo et al, 1987). This is despite mounting evidence that continually depolarized cultures undergo numerous adaptations, including perturbed patterns of AMPA (Condorelli et al, 1993), NMDA (Vallano et al, 1996), and GABA (Mellor et al, 1998) receptor subunit expression; abnormal induction of inositol 1,4,5-trisphosphate receptor (Choi et al, 2004); calpain-mediated down-regulation of Ca 2ϩ /calmodulin-dependent protein kinase type IV (Tremper-Wells and Vallano, 2005), a net decrease in synaptic vesicles (Urakubo et al, 2003); suppression of spontaneous synaptic activity and action potentials (Mellor et al, 1998); reduced VDCC currents; and increased susceptibility to death upon activity reduction (Moulder et al, 2003). On the other hand, a significant proportion of granule neurons grown in medium containing 5 mM KCl require both tetrodotoxin-sensitive Na ϩ currents and active NMDA receptors for their survival (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Rather, the amplitude, duration, and route of Ca 2ϩ influx profoundly influence cell fate (Sattler et al, 1998;Hardingham and Bading, 2002). Thus, unlike neurons grown in 5 mM KCl, continually depolarized cultures undergo numerous Ca 2ϩ -mediated adaptations (Condorelli et al, 1993;Vallano et al, 1996;Moulder et al, 2003;Choi et al, 2004;Tremper-Wells and Vallano, 2005) and are electrically silent because of Na ϩ -channel inactivation (Mellor et al, 1998). Despite this, they continue to be a favored model, whereas cultures grown in 5 mM KCl are largely ignored because a proportion dies by apoptosis 3 to 5 days after plating, a process not unlike neuronal pruning in vivo.…”
mentioning
confidence: 99%
“…Previous studies have shown that neuronal discharges (9) and subsequent activation of VDCCs (10) regulate the developmental transition of ␥-aminobutyric acid-A (GABA A ) receptor subunit expressions, a landmark of granule cell maturation (11,12). In addition, chronic depolarization-mediated Ca 2ϩ entry also differentially regulates expression of N-methyl-D-aspartate (NMDA) receptors and ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors (13)(14)(15)(16), which normally occurs during granule cell maturation (17)(18)(19). Thus, it is possible that the waggler mutation impairs cerebellar granule cell maturation and consequently causes the behavioral deficits.…”
Section: T He Waggler (Stg Wagmentioning
confidence: 99%
“…The present work investigates the developmental pattern of expression of the two receptor types in neurons and their dependence on Ca 2ϩ . As shown for other proteins involved in Ca 2ϩ signaling (6,7), IP3R expression depends on Ca 2ϩ influx, whereas RyR expression does not appear to be regulated in the same manner.…”
mentioning
confidence: 99%